Sexual dimorphism-driven differences are overcome in a preclinical vaccine model against Trypanosoma cruzi - Bulfoni Balbi, Camila; Pacini, Maria Florencia; Dinatale, Brenda; Farré, Cecilia; Cacik, Paula; Prochetto, Estefanía; González, Florencia Belén; Marcipar, Iván; Cabrera, Gabriel; Pérez, Ana Rosa (Frontiers in Immunology, 2025)
Currently, no vaccine is available to prevent Chagas disease. Experimental vaccines against Trypanosoma cruzi (Tc) have shown high protection, but their development for humans still requires further study. Additionally, the sexual dimorphism observed in Chagas disease, with greater resistance in women, highlights the need to include both sexes in vaccine research to avoid biases. To assess the impact of sex on a recombinant vaccine, its immunogenicity and efficacy after oral infection in male and female BALB/c mice were evaluated. Additionally, gonadectomized (Gx) and sham-operated (Ms) males were used to estimate testosterone’s effect. The vaccine consisted of a recombinant fragment of Tc-derived trans-sialidase (TS) formulated with a cyclic-di-adenylate known as c-di-AMP (A), administered intranasally in three doses, 2 weeks apart. Control groups received TS alone, A, or a vehicle. Immunogenicity results showed that sexual dimorphism persisted after TS+A vaccination, with females having higher TS-specific IgG2a, IgG1, IgA, IL-17, and IFN-γ levels, while males showed greater delayed-type hypersensitivity and increased TS-specific IFN-γ+ROR-γt+ T-cell proliferation. Gx-TS+A-vaccinated males showed enhanced TS-specific IgG but not IgA, with negative effects on T-cell proliferation and higher parasite loads. Notably, after oral challenge with Tc, both sexes vaccinated with TS+A controlled parasitemia, reduced tissue parasite load, improved clinical outcomes, and attenuated myocarditis. In males, the vaccine also prevented the parasite-induced increase in splenic myeloid-derived suppressor cells (MDSCs) and preserved CD4+FoxP3+ regulatory T cells. Overall, TS+A nasal vaccination enhanced protection in both sexes, overcoming sexual dimorphism and highlighting its potential for human vaccine development.